ESRA19-0131 Colonization of epidural catheters seen through the electron microscope. (30th August 2019) - Van Samkar, G; Balraadjsing, P; Hermanns, H; Hoogendijk, I; Hollmann, M; Zaat, B; Stevens, M
Abstract : Background and aims: Epidural catheters are frequently colonized by gram positive bacteria. the incidence of epidural infections is low, but their consequences can be devastating. We investigated the pattern of bacterial colonization of epidural catheters. Epidural catheters of patients showing signs of local infection were investigated by scanning electron microscopy (SEM) in order to delineate mechanism of catheter infection. Methods: 28 patients receiving thoracic epidural analgesia for more than 72 hours were studied. All received antibiotic prophylaxis after catheter placement (cefazolin, metronidazole). Skin swabs and catheter segments were cultured after catheter removal. Bacteria were identified by matrix-assisted laser desorption/ionization time of flight mass spectrometry. SEM of culture positive catheters was performed. Results: 27 of 28 catheters could be investigated. Colonization percentages were: skin swab in 22%, extracorporeal segments in 11% and subcutaneous segments in 3.7%. Cultures revealed Staphylococcus epidermidis, Staphylococcus simulans, Propionibacterium acnes, and Micrococcus luteus . In one patient, a clinically relevant infection was recorded, caused by S. epidermidis. Bacteria were cultured from extracorporeal and subcutaneous segments and the tip of this catheter. SEM displayed host cell-like structures on inner catheter surface and an intraluminal fibrin network which formatted around a catheter hole. Conclusions: Epidural catheter colonization seems to spread from the skin segments to the deeper parts of the catheter, resembling the pattern of colonization of central venous catheters. the inner surface of the catheter tip is invaded by probably immune cells and fibrin fibers forming a microfilm-like structure.